The Internet addiction and its relationship to academic achievement among students at the College of Basic Education in the State of Kuwait - الكندري, محمد; طلال المسعد; هديل الشطي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to reveal the level of Internet addiction and its relation to the educational achievement of the students of the Basic Education College of Kuwait, and to achieve its purpose researchers used the analytical descriptive curriculum; The study tool was developed using Young's measured image of the Arab environment. (Young,1996) and its translation and codification of the Arab environment Ibrahim (2009), the scale being from (20) paragraph, applied to a sample of (1,477) students from the Basic Education Faculty of the General Authority for Applied Education and Training in Kuwait. The results showed that the level of students' Internet addiction was low in general. The results showed statistical differences at the indicative level. (α=0.05) Among the computational averages of Internet addiction at the Basic Education College of Kuwait attributable to the study variable in favour of females, the results also showed a negative correlation between Internet addiction and students' educational achievement.